Activation of the macroautophagy pathway by Yersinia enterocolitica promotes intracellular multiplication and egress of yersiniae from epithelial cells. (2nd June 2019) - Valencia Lopez, Maria Jose; Schimmeck, Hanna; Gropengießer, Julia; Middendorf, Lukas; Quitmann, Melanie; Schneider, Carola; Holstermann, Barbara; Wacker, Rahel; Heussler, Volker; Reimer, Rudolph; Aepfelbacher, Martin; Ruckdeschel, Klaus
Abstract: The virulence strategy of pathogenic Yersinia spp. involves cell‐invasive as well as phagocytosis‐preventing tactics to enable efficient colonisation of the host organism. Enteropathogenic yersiniae display an invasive phenotype in early infection stages, which facilitates penetration of the intestinal mucosa. Here we show that invasion of epithelial cells by Yersinia enterocolitica is followed by intracellular survival and multiplication of a subset of ingested bacteria. The replicating bacteria were enclosed in vacuoles with autophagy‐related characteristics, showing phagophore formation, xenophagy, and recruitment of cytoplasmic autophagosomes to the bacteria‐containing compartments. The subsequent fusion of these vacuoles with lysosomes and concomitant vesicle acidification were actively blocked by Yersinia . This resulted in increased intracellular proliferation and detectable egress of yersiniae from infected cells. Notably, deficiency of the core autophagy machinery component FIP200 impaired the development of autophagic features at Yersinia ‐containing vacuoles as well as intracellular replication and release of bacteria to the extracellular environment. These results suggest that Y .  enterocolitica may take advantage of the macroautophagy pathway in epithelial cells to create an autophagosomal niche that supports intracellular bacterial survival, replication, and, eventually, spread of the bacteria from infected cells.